2022
DOI: 10.1111/bpa.13058
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of autophagy‐related p62 without increased deposits of neurodegeneration‐associated proteins in glioblastoma and surrounding tissue – An autopsy‐based study

Abstract: Neurodegenerative diseases are a major health burden. The underlying causes are not yet fully understood, but different mechanisms such as cell stress and chronic inflammation have been described as contributing factors. Neurodegenerative changes have been observed in the vicinity of brain tumors, typically around slowly growing benign lesions. Moreover, in‐vitro data suggest a potential induction of pathological tau deposits also in glioblastoma, a highly malignant and proliferative brain cancer. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…This study suggested a direct link between AD and GBM or that GBM might promote neurodegeneration rather than oppose it [15]. Another study posited that neurodegeneration occurs before tumor formation, given that post-mortem GBM samples showed neurodegenerative-associated proteins, such as Aβ and tau, present in the majority of cases but in distant sites and in an age-expected amount and distribution compared to controls [3].…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…This study suggested a direct link between AD and GBM or that GBM might promote neurodegeneration rather than oppose it [15]. Another study posited that neurodegeneration occurs before tumor formation, given that post-mortem GBM samples showed neurodegenerative-associated proteins, such as Aβ and tau, present in the majority of cases but in distant sites and in an age-expected amount and distribution compared to controls [3].…”
Section: Discussionmentioning
confidence: 82%
“…Both glioblastoma (GBM) and dementia are devastating diseases with limited treatments that are usually not curative [1]. Having clinically diagnosed dementia with an associated biopsy-proven etiology and a coexisting GBM diagnosis is a rare occurrence [2,3]. The relationship between the development of neurodegenerative dementia and GBM is unclear [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations